Kontribusi Pemikiran Tokoh Feminisme Islam - Tarhan, Raden Muhammad; Syukur, Syamzan; Rahmawati, Rahmawati (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
Women in Islamic studies have reached a very important position. Many gender activists have discussed this topic, especially regarding gender equality. Several prominent feminist figures in the struggle for women's rights and gender equality include Qasim Amin, Amina Wadud Muhsin, and Fatimah Mernissi. Each of them has their own views about women. This article was prepared with the aim of presenting several opinions from these feminist figures and then extracting them. The writing of this article applies library research methods by collecting library materials sourced from books, journals and online articles. Based on this study, the view is obtained that Islamic feminist thought is very influential in reconstructing the interpretation of the position of women in Islamic law. This is a form of confirmation that interpretation is a subjective matter that is greatly influenced by the interpreter. Muslim feminist thought is actually relevant to the current context where men and women have equal positions.